Regional Aspects of New Industrialization - Silin, Yakov Petrovich; Animitsa, Yevgeniy Georgievich; Novikova, Natalya Valeryevna (Economy of Regions, 2017)
In the article, the authors substantiate the need to consider the regional economic and other conditions when carrying out various essential transformations in the national economy of the country. We have argued the importance of new industrialization for overcoming the technological lag of the country and its regions and for supporting the large-scale structural transformations. We have proved that the complex set of the interconnected concepts and the theories of macro- and microlevels may be the theoretical platform for the paradigm of new industrialization. These are the theory of economic growth, the theory of the modernization of the economy, the theory of the change of technological ways during the industrial revolutions, theories of innovative development, developments in the field of the institutional theory. The authors have shown that the transition to new industrialization is the fundamental historical pattern for the majority of the countries of the world, including industrially developed ones. The purpose of the article is to identify the brightest tendencies and features of the development of the Ural macro-region in the years of market reforms as well as the definition of the strategic transformations in the context of the formation of new industrialization. The hypothesis of the research assumes that the revealed regional features of the Ural macroregion's economic development are the prerequisites of its development as the centre of the modernization of the Russian economy. On the basis of the analysis of three groups of statistic data for the twenty-five year period of liberal and monetary reforms, the brightest tendencies and features of the development of the Ural macro-region are revealed. We have emphasized that the Ural macro-region has managed to keep its historically developed code - the industrial model of the economy, which have been developing for many decades. The authors have made a significant contribution of new statistical information to the knowledge of regional economy because, since 2000, the regional statistics in the country have been operated to the data on federal districts, but not on large economic districts. We have allocated and considered several strategic directions of the structural transformations promoting the activation of the processes of the formation of new industrialization in the space of studied macro-region. The results of the research can serve as a reference point for the strategies of regional development.